ASAS PRADUGA TIDAK BERSALAH: PENERAPAN DAN PENGATURANNYA DALAM HUKUM ACARA PERDATA - Butarbutar, E. Nurhaini (Jurnal Dinamika Hukum, 2011)
The principle of  presumption of innocence, was a general  principle of procedural law, because that was contained in the Act of Power by Judiciary. As that the general principle of procedural laws, that was principle has been effective to all process matter in the court. But also, the principle of  presumption of innocence, only well known in the criminal process matter because that was back arrenged in KUHAP and was not arranged in HIR/Rbg as a regulation of civil procedural in the court. Nevertheless, the principle of presumption of innocence was applied in civil process matter by mean of the implementation of principle that contained in HIR/Rbg, i.e principle of actor sequitor forum rei, principle of equality before the law and principle of actori in cumbit probation. Key words : The principle of presumption of innocence, a general principle of procedural law, its implementation, civil process matter